2022
DOI: 10.3390/ijms232112769
|View full text |Cite
|
Sign up to set email alerts
|

A Heat Shock Transcription Factor TrHSFB2a of White Clover Negatively Regulates Drought, Heat and Salt Stress Tolerance in Transgenic Arabidopsis

Abstract: Heat shock transcription factors (HSF) are divided into classes A, B and C. Class A transcription factors are generally recognized as transcriptional activators, while functional characterization of class B and C heat shock transcription factors have not been fully developed in most plant species. We isolated and characterized a novel HSF transcription factor gene, TrHSFB2a (a class B HSF) gene, from the drought stress-sensitive forage crop species, white clover (Trifolium repens). TrHSFB2a was highly homologo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Plants share common regulatory signals or pathways in response to abiotic stresses such as high temperature, drought, and high salt [22,23]. Among the 1931 high temperature responsive genes we screened, more than half responded to both drought and high salt stress simultaneously (Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…Plants share common regulatory signals or pathways in response to abiotic stresses such as high temperature, drought, and high salt [22,23]. Among the 1931 high temperature responsive genes we screened, more than half responded to both drought and high salt stress simultaneously (Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a novel gene DUF569 (AT1G69890) with "domain of unknown function" positively regulates drought stress in Arabidopsis (Nabi et al, 2021). The HSF transcription factor gene TrHSFB2a (B-type HSF), which was recently identified in drought-sensitive white clover (Trifolium repens), negatively regulates drought resistance (Iqbal et al, 2022) (Figure 3B). Under drought stress conditions, overexpression of the ONAC066 gene (a novel gene whose function has been newly determined) enhances the tolerance of rice to drought stress and sensitivity to ABA (Yuan et al, 2019).…”
Section: Drought Stressmentioning
confidence: 99%
“…TrHSFB2a expression in white clover was strongly induced by exposure to high temperature (35°C) and the encoded protein negatively regulates heat tolerance (Iqbal et al, 2022). The POFs in Arabidopsis enhance plant tolerance to oxidative stress under both cold and heat stress (Luhua et al, 2008) (Figure 3C).…”
Section: Extreme Temperature Stressmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that HSF members are markedly associated with plant development and various stress responses, such as responses to freezing and salt, drought, and high-temperature tolerance [ 5 , 7 , 22 , 23 , 24 , 25 , 26 ]. In plants, HSF genes are the primary modulator of high-temperature stress [ 22 ].…”
Section: Introductionmentioning
confidence: 99%